The affective curriculum : teaching the anti-bias approach to young children - Hall, Nadia Saderman; Rhomberg, Valerie (Toronto : Nelson Canada, 1995)
An introduction to the anti-bias approach. Exploring one's values and attitudes. Living in a diverse world with sensitivity. Curriculum design for an anti-bias program. Curriculum design for infants and toddlers...
Keywords: Education; Curricula; Activity programs; Discrimination in education; Childhood education; Prejudices; Early childhood education -- Activity programs; Education -- Childhood education -- Curricula; Prejudices -- Study and teaching (Preschool); Social values -- Study and teaching (Preschool); Discrimination in education